2016
DOI: 10.3389/fmed.2016.00049
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Resolution of Chronic Diarrhea Likely Due to Crohn’s Disease and Infection with Mycobacterium avium paratuberculosis

Abstract: Examination of samples of stool from a 61-year-old male patient, presenting with the clinical symptoms of Crohn’s disease (CD), revealed massive shedding of acid fast bacilli with the morphology of Mycobacterium avium paratuberculosis (MAP), the causative agent of Johne’s disease in cattle. MAP was cultured from the stool. Biotyping of the bacterium isolated from cultures of stool demonstrated, it was the Indian Bison biotype of MAP, the dominant biotype infecting livestock and humans in India. Based on this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The study also showed that one repeat (7g-4ggt) was common to the original isolates obtained by Chiodini et al (cited in [31,32]). This same repeat sequence was also found in the Map isolate obtained from the patient in the case report described here [12], and this isolate is the predominant form found in the environment, livestock, and humans in India. This similarity suggests that screening will reveal limited diversity in the isolates obtained from humans.…”
Section: The Third Stepsupporting
confidence: 78%
See 1 more Smart Citation
“…The study also showed that one repeat (7g-4ggt) was common to the original isolates obtained by Chiodini et al (cited in [31,32]). This same repeat sequence was also found in the Map isolate obtained from the patient in the case report described here [12], and this isolate is the predominant form found in the environment, livestock, and humans in India. This similarity suggests that screening will reveal limited diversity in the isolates obtained from humans.…”
Section: The Third Stepsupporting
confidence: 78%
“…Other than the massive shedding of Map in his feces, the clinical features of the patient's disease were indistinguishable from the clinical features of patients with CD. Treatment with anti-Map antibiotics cleared the infection with Map and concurrently cured the patient of the clinical features of CD [12]. In two other case reports, patients with classic CD and blood cultures positive for Map were treated with anti-Map therapy.…”
Section: Is It Johne's Disease or Crohn's Disease?mentioning
confidence: 99%
“…A strong association has been documented between MAP and Crohn's disease (Waddell et al, 2015), but important knowledge gaps to establish the causal path still exist (More et al, 2017). Genetic mimicry between protein epitopes of MAP and human proteins have been associated with autoimmune disorders (Davis, 2015;Sechi and Dow, 2015;Singh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly other workers have also reported involvement of MAP in clinical symptoms and gross pathology of Crohn's disease (CD) in human beings and Johne's disease in animals [6][7][8]. In India, MAP has also been recovered from chronic patients of CD [9], suspected animal workers [10], human population from peri-urban areas [11], mass screening of human samples [1] and of patients suffering with advance clinical stage of CD [12].…”
Section: Introductionmentioning
confidence: 95%